Unveiling Cas8 dynamics and regulation within a transposon-encoded Cascade–TniQ complex - Amun C. Patel; Souvik Sinha; Pablo R. Arantes; Giulia Palermo (Proceedings of the National Academy of Sciences, 2025)
The Vibrio cholerae Cascade–TniQ complex unveiled a new paradigm in biology, demonstrating that CRISPR-associated proteins can direct DNA transposition. Despite the tremendous potential of “knocking-in” genes at desired sites, the mechanisms underlying DNA binding and transposition remain elusive. In this system, a conformational change of the Cas8 protein is essential for DNA binding, yet how it occurs is unclear. Here, structural modeling and free energy simulations reconstruct the Cas8 helical bundle and reveal an open–closed conformational change that is key for the complex’s function. We show that when Cascade–TniQ binds RNA, the Cas8 bundle changes conformation mediated by the interaction with the Cas7.1 protein. This interaction promotes the bundle’s transition toward the open state, priming the complex for DNA binding. As the target DNA binds the guide RNA, the opening of the Cas8 bundle becomes more favorable, exposing positively charged residues and facilitating their interaction with DNA, which ultimately leads the DNA-binding process to completion. These outcomes provide a dynamic representation of a critical conformational change in one of the largest CRISPR systems and illustrate its role at critical steps of the Cascade–TniQ biophysical function, advancing our understanding of nucleic acid binding and transposition mechanisms.